Towards map-based cloning of Fusarium head blight resistance QTL Fhb1 and non-additive expression of homoeologous genes in allohexaploid wheat - Pumphrey, Michael Odell (Kansas State University, 2007)
Wheat is the most widely grown and consumed grain crop in the world. In order to meet future agricultural production requirements of a growing population, it is essential that we achieve an increased understanding of the basic components and mechanisms shaping growth and productivity of the polyploid wheat plant. Fusarium head blight (FHB) (syn. "scab") poses a serious threat to the quantity and safety of the world's food supply. The resistance locus Fhb1 has provided partial resistance to FHB of wheat for nearly four decades. Map-based cloning of Fhb1 is justified by its significant and consistent effects on reducing disease levels, the importance of FHB in global wheat production and food safety, and because this gene confers partial resistance to this disease and does not appear to behave in a gene-for-gene manner. A bacterial artificial chromosome (BAC) contig spanning the Fhb1 region was developed from the cultivar 'Chinese Spring', sequenced and seven candidate genes were identified in an ~250 kb region. Cosmid clones for each of the seven candidate genes were isolated from a line containing Fhb1 and used for genetic transformation by biolistic bombardment. Transgenic lines were recovered for five candidate genes and evaluated for FHB resistance. All failed to complement the Fhb1 phenotype. Fhb1 is possibly one of the two remaining candidate genes, an unknown regulatory element in this region, or is not present in Chinese Spring. Traditional views on the effects of polyploidy in allohexaploid wheat have primarily emphasized aspects of coding sequence variation and the enhanced potential to acquire new gene functions through mutation of redundant loci. At the same time, the extent and significance of regulatory variation has been relatively unexplored. Recent investigations have suggested that differential expression of homoeologous transcripts, or subfunctionalization, is common in natural bread wheat. In order to establish a timeline for such regulatory changes and estimate the frequency of non-additive expression of homoeologous transcripts in newly formed T. aestivum, gene expression was characterized in a synthetic T. aestivum line and its T. turgidum and Aegilops tauschii parents by cDNA-SSCP and microarray expression experiments. The cDNA-SSCP analysis of 30 arbitrarily selected homoeologous transcripts revealed that four (~13%) showed differential expression of homoeoalleles in seedling leaf tissue of synthetic T. aestivum. In microarray expression experiments, synthetic T. aestivum gene expression was compared to mid-parent expression level estimates calculated from parental expression levels. Approximately 16% of genes were inferred to display non-additive expression in synthetic T. aestivum. Six homoeologous transcripts classified as non-additively expressed in microarray experiments were characterized by cDNA-SSCP. Expression patterns of these six transcripts suggest that cis-acting regulatory variation is often responsible for non-additive gene expression levels. These results demonstrate that allopolyploidization, per se, results in rapid initiation of differential expression of homoeologous loci and non-additive gene expression in synthetic T. aestivum.
Keywords: Wheat; Polyploidy; Microarray expression; Fusarium; Homoeologous; Fhb1